Integrating Branding, Advertising, and Selling to Achieve Competitive Advantage for SMEs - Muhammad Fahmi; Muhammad Taufik Lesmana; Muhammad Andi Prayogi; Rini Astuti (International Journal of Business Economics (IJBE), 2026)
Purpose –  This study aims to analyse the influence of the Destination, Origin, Time (DOT), Paid Media, Owned Media, Social Media, and Endorser (POSE) approaches on competitive advantage, and to examine the moderating role of Branding, Advertising, and Selling (BAS) in MSMEs in Medan City.Method –  This study used a quantitative approach, involving 385 MSMEs as the research sample. Data were collected through a survey and analysed using Partial Least Squares (PLS)-based Structural Equation Modelling (SEM), which is appropriate for examining complex relationships among variables.Results –  The results show that Destination, Origin, Time (DOT), Paid Media, Owned Media, Social Media, Endorser (POSE), and Branding, Advertising, and Selling (BAS) significantly influence competitive advantage. Furthermore, Branding, Advertising, and Selling (BAS) were shown to act as moderating variables, strengthening the relationship between marketing strategy and SMEs competitive advantage.Novelty –  The novelty of this research lies in the integration of the DOT, POSE, and BAS models into a single conceptual framework to explain the achievement of competitive advantage in SMEs. This research also expands the strategic marketing literature by positioning BAS as a moderating variable, a topic that has not been widely studied in the context of MSMEs in Indonesia.Implications – This research provides practical implications for MSMEs to optimise DOT- and POSE-based marketing strategies by strengthening branding, advertising, and sales to enhance competitive advantage. These findings can also serve as a reference for local governments and stakeholders when designing SMEs development programs to increase business competitiveness.